Pembangunan Di Kabupaten Pegunungan Bintang (Studi Kasus : Desa Denom Atukbin, Distrik Pepera) - Normalia Ode Yanthy; Y.L.M. Sitorus (PLANNERS INSIGHT : URBAN AND REGIONAL PLANNING JOURNAL, 2019)
Various development acceleration programs planned for the Papua region rely more on development capital from outside Papua and pay little attention to development capital from within, such as: human capital, social and cultural Papuans themselves. Development towards modernization in Papua without relying on existing local development capital will require enormous funds because civilizations in this region are still lagging behind. The study area in this study is Denom Atukbin Village which is planned to develop into an independent city. This study uses a qualitative research approach with descriptive analysis methods. The limitation of development capital of local human resources (the quantity and quality of human beings is still low) and supporting facilities (infrastructure is still minimal) shows that the implementation of the development plan prepared by the Pegunungan Bintang Regency government will require greater funds (because it uses development capital from outside). In the process, the original inhabitants of Denom Atukbin Village are not expected to be involved much or not the main actors of the development.